Comparative Study of Conventional Rotary and Rotary-Percussion Techniques in Grout Hole Drilling from the Perspectives of Time, Cost, and Quality - Dika Prasetyo; Setya Winarno (Institute of Research and Community Outreach - Petra Christian University, 2023)
A dam foundation structure is usually strengthened by grouting, which begins with grout hole drilling. This paper aims to examine a comparison between conventional rotary and rotary-percussion drilling techniques in a drilling case study of the Tugu Dam Project, from the perspective of time, cost, and quality comprehensively. Primary data was obtained from the field investigation and interviews. Secondary data was gathered from available project documents of the PT Wijaya Karya-APTA KSO Project Contractor. The findings have highlighted that the implementation of the rotary-percussion technique for grout hole drilling is better than conventional rotary drilling. There are 16 days of time-saving and 3.84% cost-savings for the rotary-percussion technique, as a result of faster rate of penetration. The quality of grouting work using the rotary-percussion drilling technique tends to be of better quality, although there is a shortcoming due to the limited drilling depth of only 5m particularly.